2015
DOI: 10.1177/1748895815599582
|View full text |Cite
|
Sign up to set email alerts
|

Desistance and the micro-narrative construction of reformed masculinities in a Danish rehabilitation centre

Abstract: Juvenile justice systems and reformatory institutions hold the potential to help young offenders and drug abusers change their behaviours and life-courses. Driven by an ambition to pave new ways to examine the inner workings of reformatory institutions this study explores how young male offenders' gendered identities are engaged in a Danish reformatory programme. In recent years existing research on the gendered aspects of reformatory interventions has highlighted how reformatory institutions at times work to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 41 publications
(61 reference statements)
3
32
0
2
Order By: Relevance
“…; Søgaard et al . ). As studies have shown, desistance cannot occur without relevant social, emotional or psychological transitions as well as individual agency and the construction of events as meaningful (Carlsson ; Liebregts et al .…”
Section: Conceptual Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…; Søgaard et al . ). As studies have shown, desistance cannot occur without relevant social, emotional or psychological transitions as well as individual agency and the construction of events as meaningful (Carlsson ; Liebregts et al .…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…More recently, however, criminologists have convincingly argued that desistance is not just about transformations of offenders' circumstances. Desistance is best understood as a gradual process, characterised by 'turning points', progression and relapse (Carlsson 2012), as well as (inter)subjective processes, such as cognitive transformations and personal narrative reconstructions of selves and identities (Maruna 2001;Gadd and Farrall 2004;Giordano et al 2008;Søgaard et al 2015). As studies have shown, desistance cannot occur without relevant social, emotional or psychological transitions as well as individual agency and the construction of events as meaningful (Carlsson 2012;Liebregts et al 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…We thematically coded and analysed field notes and interviews using established ethnographic iterative techniques of continuous comparison and triangulation of data. Importantly, observations showed that NS constitutes a rehabilitation programme that uses particular masculinized meta-narratives, derived from the world of boxing, to communicate values of individual willpower and self-responsibility to the young participants (see also: Søgaard et al 2016). Thus, NS is an example of how neo-liberal and individualist discourses are gaining prominence in Scandinavian welfare institutions (Franzén 2015).…”
Section: Methods and Datamentioning
confidence: 99%
“…Importantly, however, little attention has been given to ethnic minority men's experiences and cultural formations in later stages of their criminal, drug or gang careers (exceptions include: Calverley, 2013;Glynn, 2014;Moloney et al, 2009). This is particularly true in the Scandinavian context where qualitative research on ethnic minority men's desistance processes from crime, drug or gang involvement is almost absent (exceptions include: Sandberg, 2010a;Søgaard et al, 2016). In Denmark, the reason for little research may be related to the fact that only recently did ethnic minority youth street gangs become a high priority problem on the political agenda (Bengtsson 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Canaan (1996) emphasized that the participation of young men in fights is sometimes regarded as a kind of proof of masculinity: it shows that they can control themselves and their opponents and that they can withstand possible physical pain. In a study of a Danish reform program that involved boxing practice, as well as other activities, the researchers illustrate how such a program may be successful because it draws on willpower, autonomy, and challenges, traits that are celebrated in the street cultures that the young men come from (Friis Søgaard, Kolind, and Thystrup 2016). In this sense, the role of victim is also gender-related in that playing down the seriousness of the crime and one's own victimization may be a way to portray masculinity (Burcar 2005(Burcar , 2013.…”
Section: Research On Reporting Crimes To the Policementioning
confidence: 99%